The adhesion of homogenized fat globules to proteins is increased by milk heat treatment and acidic pH: Quantitative insights provided by AFM force spectroscopy. (March 2020) - Obeid, Sameh; Guyomarc'h, Fanny; Tanguy, Gaëlle; Leconte, Nadine; Rousseau, Florence; Dolivet, Anne; Leduc, Arlette; Wu, Xiaoxi; Cauty, Chantal; Jan, Gwénaël; Gaucheron, Frédéric; Lopez, Christelle
Graphical abstract: Highlights: Homogenization and UHT heat treatment alter the surface properties of milk fat globules. AFM allows nanoscale measurement of the adhesion forces between fat globules and proteins. UHT and acidic pH increase the adhesion forces between homogenized fat globules and proteins. Process-induced changes govern the microstructure and rheology of dairy acid gels. Abstract: The rheological properties and microstructure of dairy gels involve the connectivity between milk fat globules (MFG) and casein micelles that is affected by technological processes such as milk homogenization and heat treatment. The underlying mechanisms require further quantification of the interactions at the nanoscale level to be fully understood and controlled. In this study, we examined the adhesion of homogenized MFG to milk proteins and evaluated the role of ultra-high temperature (UHT) heat treatment and pH. The combination of physico-chemical analysis, rheology and microscopy observations at different scale levels associated to atomic force microscopy (AFM) force spectroscopy were used. AFM experiments performed at the particle scale level showed that adhesion of individual homogenized MFG to milk proteins (1) is increased upon acidification at pH 4.5: 1.4 fold for unheated samples and 3.5 fold for UHT samples, and (2) is enhanced by about 1.7 fold at pH 4.5 after UHT heat treatment of milk, from 176 pN to 296 pN, thanks to highly-reactive heat-denatured whey proteins located at the surface of MFG and caseins. The increased inter-particle adhesion forces accounted for more connected structures and stiffer UHT milk acid gels, compared to unheated-milk gels. Using a multiscale approach, this study showed that heat treatment of milk markedly affected the interactions occurring at the particle's surface level with consequences on the bulk structural and rheological properties of acid gels. Such findings will be useful for manufacturers to modulate the texture of fermented dairy products through the tailoring of heat-induced complexation of proteins and the connectivity of homogenized MFG with the protein network. This work will also contribute in a better understanding of the impact of process-induced changes on the digestibility and metabolic fate of proteins and lipids.